2013
DOI: 10.1039/c3cc43797c
|View full text |Cite
|
Sign up to set email alerts
|

Mechano-isomerization of azobenzene

Abstract: We show that ultrasound-induced mechanical force isomerizes an azobenzene centered within a poly(methyl acrylate) polymer from cis to trans configuration without cleaving the azo bond. The isomerization rate was not altered by the polarity of the solvent indicating that the isomerization occurs through a non-polar, inversion transition state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 22 publications
1
36
0
Order By: Relevance
“…A strong relationship between rate of reactions and solvent polarity points to an intermediate transition state that is considerably more polar than the cis conformation. This polar transition state is indicative of a rotational mechanism for the isomerization of 4A4NAB [21,22,24]. This result is expected considering the strong electron withdrawing group (the nitro group) on 4A4NAB and is corroborated by computational studies [22,25,26].…”
supporting
confidence: 70%
“…A strong relationship between rate of reactions and solvent polarity points to an intermediate transition state that is considerably more polar than the cis conformation. This polar transition state is indicative of a rotational mechanism for the isomerization of 4A4NAB [21,22,24]. This result is expected considering the strong electron withdrawing group (the nitro group) on 4A4NAB and is corroborated by computational studies [22,25,26].…”
supporting
confidence: 70%
“… 34 claimed that mechanoisomerization of azobenzene typically results in the cleavage of the N=N azo bond. However, more recent theoretical calculations 35 and experiments 36 have challenged this view.…”
Section: Resultsmentioning
confidence: 99%
“…2b . Previous studies 36 37 on the trans -to- cis isomerization of azobenzene in the presence of UV light showed that the reaction follows first-order kinetics and the rate constant k can be written as follows:…”
Section: Resultsmentioning
confidence: 99%
“…Only recently, after studies of the molecular physics of the photoisomerization of azo dyes have revealed that the photoisomerization reaction occurs on the timescale of a few picoseconds (2,3), azobenzenes came back into focus as potential photoswitchable materials (4,5). Azobenzenes have been investigated in terms of ultrafast spectroscopy (4, 6, 7), mechanoisomerization (8), the effect of slow photons (9), two-photon absorption (10) and laser-induced periodic surface structuring (11)(12)(13)(14)(15)(16)(17). The latter describes the phenomenon of Turing pattern formation on the surface of an azopolymer film upon exposure to UV or visible light.…”
mentioning
confidence: 99%